Microbial Processing of Jellyfish Detritus in the Ocean - Tinta, Tinkara; Zhao, Zihao; Escobar, Alvaro; Klun, Katja; Bayer, Barbara; Amano, Chie; Bamonti, Luca; Herndl, Gerhard J. (Frontiers in Microbiology, 2020)
When jellyfish blooms decay, sinking jellyfish detrital organic matter (jelly-OM), rich in proteins and characterized by a low C : N ratio, becomes a significant source of OM for marine microorganisms. Yet, the key players and the process of microbial jelly-OM degradation and the consequences for marine ecosystems remain unclear. We simulated the scenario potentially experienced by the coastal pelagic microbiome after the decay of a bloom of the cosmopolitan Aurelia aurita s.l.. We show that about half of the jelly-OM is instantly available as dissolved organic matter and thus, exclusively and readily accessible to microbes. During a typical decay of an A. aurita bloom in the northern Adriatic Sea about 100 mg of jelly-OM L-1 becomes available, about 44 µmol L-1 as dissolved organic carbon (DOC), 13 µmol L-1 as total dissolved nitrogen, 11 µmol L-1 of total hydrolysable dissolved amino acids (THDAA) and 0.6 µmol L-1 PO43-. The labile jelly-OM was degraded within 1.5 days (> 98% of proteins, ~ 70% of THDAA, 97% of dissolved free amino acids and the entire jelly-DOC pool) by a consortium of Pseudoalteromonas, Alteromonas and Vibrio. These bacteria accounted for > 90% of all metabolically active jelly-OM degraders, exhibiting high bacterial growth efficiencies. This implies that a major fraction of the detrital jelly-OM is rapidly incorporated into biomass by opportunistic bacteria. Microbial processing of jelly-OM resulted in the accumulation of tryptophan, dissolved combined amino acids and inorganic nutrients, with possible implications for biogeochemical cycles.